Distribution pattern of mesangial C4d deposits as predictor of kidney failure in IgA nephropathy. - Suchin Worawichawong; Sirithep Plumworasawat; Wisit Liwlompaisan; Vasant Sumethkul; Bunyong Phakdeekitcharoen; Umaporn Udomsubpayakul; Panus Chalermsanyakorn; Chagriya Kitiyakara (PLoS ONE, 2021)
Mesangial C4d deposits have been associated with worse outcomes in Western patients with IgA nephropathy (IgAN), but there is limited data in Asians. Previously, a high proportion of stained glomeruli was often required for the classification of C4d positive (C4d+ve). Positive staining in lower proportion of staining would be classified as C4d-ve. This retrospective study evaluated the prognostic value of C4d+ve using a less stringent definition (one C4d+ve glomerulus) in Thai patients with IgAN (n = 120). Baseline findings and outcomes were compared between those with more extensive C4d staining patterns and those with more restricted staining. Clinico-pathologic parameters and risk for kidney outcomes (kidney failure or decline GFR50%) were compared between C4d+ve versus C4d-ve, and between different patterns: Focal (< 50%) versus Diffuse (≥ 50% of glomeruli); or Global (≥ 50) versus Segmental (< 50% of mesangial area). The hazard ratios were estimated using Cox proportional hazard models for Model 1 (Oxford score+ C4d) and Model 2 (Model 1+ clinical factors). C4d+ve (n = 81) had lower eGFR, more global sclerosis, and interstitial fibrosis than C4d-ve at baseline. The 5-year kidney survival for C4d+ve was lower (53.7%) than C4d-ve (89.7%); P = 0.0255. By univariate analysis, T1, T2, C4d+ve, eGFR<60, proteinuria were predictors of kidney outcome. By multivariate analysis, proteinuria, T1, T2 and C4d+ve were independent predictors (Model 2 HR (95% CI) C4d+ve: 3.24 (1.09-9.58), p = 0.034). Segmental had lower eGFR, higher tubulointerstitial fibrosis, and segmental sclerosis compared to Global pattern. Clinicopathological parameters were not different between Focal and Diffuse patterns. Outcomes were similar between staining patterns. In conclusion, C4d staining may be a valuable marker of poor prognosis in Asian patients with IgAN. Less stringent criteria for C4d+ve should be considered as no differences in outcomes were observed between more extensive staining with less extensive patterns. More studies are needed to identify the optimum criteria for C4d+ve.